Analisis Bisnis Model Kanvas dan Kelayakan Keuangan (Studi Kasus Pada Teri Sambal Terateri) - Petrus Salamin; Francisca Hermawan (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2017)
Tujuan penelitian – to observe whether or not feasible if done online and offline sales “sambal teri” merk Tera Teri and how Business model canvas at its business model elements 9.Desain/Metodologi/Pendekatan – The data that we get for this research, namely secondary data obtained at the library, trade organizarrions, the Central Bureau of statistics “sambal teri” merk Tera Teri business is a business that generates side dishes prepared with typical consumption of Indonesia. Temuan - Financial feasibility calculation results, value NPV TeraTeri > 0, amounting to Rp 1.159.716.330 for which it can be concluded that the business is eligible to run. Payback period that is required is for 1 year 5 months 4 days.Keterbatasan penelitian - The intended customer segment by TeraTeri is anyone interested in the chili sauce and “ikan teri” in the region of DKI Jakarta and focused customer segments, namely employees who do not have much time to cook and can't cook so choose food ready consumptionOriginality/value – Customer Relationship Tera Teri activity, using social media like Instagram and Line with all customers